Conservative management of isolated medial subtalar joint dislocations in volleyball players: a report of three cases and literature review - Biz, C.; Ruaro, A.; Giai Via, A.; Torrent, J.; Papa, G.; Ruggieri, P. (The Journal of Sports Medicine and Physical Fitness, 2019)
Isolated subtalar dislocations (SDs) are rare injuries, representing only 1% of all foot traumas. In the current literature, only a few reports have described this acute injury as a consequence of low-middle-energy trauma during sports activities and none in professional or recreational volleyball players. Further, to the best of our knowledge, no validated standard rehabilitation programs have been described for SDs as most of them are usually treated like an ankle sprain. This report describes 3 cases of isolated, closed medial SD, which occurred during non-professional volleyball activities. All cases were successfully treated by the same conservative method: standard radiographs for diagnosis, closed reduction, subsequent CT scan to exclude associated lesions, 4-week immobilization in a below-knee cast and an early physiokinesis therapy program. Further, a review of the recent literature concerning SD was performed. The standard method applied allowed our patients to return to full sports activity at 3 months from trauma, reaching a medium AOFAS score of 96.6 at minimum follow-up of 48 months. The treated cases and the review of the literature suggest that a conservative method and early mobilization should be the first-choice treatment for closed SD, even in volleyball players. Despite the absence of a sport-specific rehabilitation program for these injuries, early physiokinesis therapy, after no more than 4-week immobilization period, allowed the improvement of our patients` hindfoot stability and their fast return to full sports activities, without any recurrence at minimum follow-up of 2 years.